Dampak Sosial Ekonomi Keberadaan Umkm Briket Cangkang Sawit Terhadap Masyarakat Desa Riak Siabun Kabupaten Seluma - Ahmad Aji Wibowo; Herri Fariadi; Ana Nurmalia (PUCUK : Jurnal Ilmu Tanaman, 2025)
Riak Siabun Village, Seluma Regency, one of the areas in Bengkulu Province has a lot of potential for palm kernel shells. In the last few years, one of the palm shell briquette MSMEs in this village has shown that waste from palm shells can be utilized and has economic value after being made into palm shell briquettes. This influence not only covers economic aspects, but also social aspects. The aim of this research is to evaluate the social impact of the existence of palm shell briquette MSMEs in Riak Sibun Village, Seluma Regency and to evaluate the economic impact of the existence of palm shell briquette MSMEs on the community in Riak Siabun Village, Seluma Regency. The method used is a qualitative method. The results of the research show that the social impact felt by the people of Riak Siabun Village is living more productively using time, this was approved by 78 people, reducing waste was approved by 70 people, and improving lifestyle was approved by 63 people. Meanwhile, the economic impact of causing labor absorption was approved by 83 people, then increased employment was approved by 81 people and the addition of alternative energy was approved by 75 people. Community income from the sale of palm shell waste to MSMEs of palm shell briquettes is IDR. 2,800,000/ month. These results were obtained through interviews with the community.